2019
DOI: 10.1590/1980-5373-mr-2019-0343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-pressure Torsion on Corrosion Behavior of a Solution-treated Al-Mg-Sc Alloy in a Saline Solution

Abstract: The effect of the increase in crystalline defects in the structure generated by high-pressure torsion (HPT) on the corrosion behavior of metallic materials is not well understood. This report evaluates the influence of HPT on the corrosion behavior of a solution treated Al-3wt% Mg-0.2wt% Sc alloy in a 3.5 wt./v.% NaCl solution. The electrochemical behavior of the alloy was evaluated using cyclic polarization, electrochemical impedance spectroscopy (EIS), Mott Schottky, X-ray photoelectron spectroscopy, and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…It should be noted that the values for the dislocation density in this study show the same trend as in a recent study even though a different method was used to estimate ρ [65]. The microstructure of the 10-HPT-RT material has slightly elongated grain structures with an average size of ~150 nm, where this is similar to earlier investigations after processing different Al-3Mg alloys by HPT at RT [22,45,48,69,70]. Additionally, the clearly defined rings in the SAED pattern in Fig.…”
Section: Microstructural Evolutionsupporting
confidence: 85%
“…It should be noted that the values for the dislocation density in this study show the same trend as in a recent study even though a different method was used to estimate ρ [65]. The microstructure of the 10-HPT-RT material has slightly elongated grain structures with an average size of ~150 nm, where this is similar to earlier investigations after processing different Al-3Mg alloys by HPT at RT [22,45,48,69,70]. Additionally, the clearly defined rings in the SAED pattern in Fig.…”
Section: Microstructural Evolutionsupporting
confidence: 85%
“…Therefore, OCP can be a thermodynamic indicator for a relative driving force for the reaction and be a kinetics indicator for a relative corrosion rate. It can be observed from Table 2 that the OCP values are lower than those reported in previously mentioned literature: −0.89 V versus SCE for Al-Zn-Mg-Cu-Sc, 16 −0.93 V versus SCE for deformed Al-Mg, 38 −1.0 V Ag/AgCl for Al-Mg-Sc, 39 and −0.96 V Ag/AgCl for Al-Mg, 40 even though the alloys share a similar composition, despite variations in composition and alloying elements. However, in our study, the majority of OCP values are notably low, exceeding −1 V versus SCE.…”
Section: Densification Behaviormentioning
confidence: 61%
“…In contrast to the HPT, electrochemical tests were used in the research on Al-Mg-Sc alloy conducted in a sodium chloride solution. The findings of the cyclic polarization test and Electrochemical Impedance Spectroscopy (EIS) showed that the surface of the alloy underwent the formation of a stronger protective oxide layer as a consequence of the HPT treatment [12]. Beura et al [13] investigated the corrosion behavior of the Al5083 alloy subjected to forward Taylor anvil experiments at various velocities.…”
Section: Introductionmentioning
confidence: 99%